2002
DOI: 10.1093/bja/89.3.428
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of midazolam and its 1-hydroxy metabolite to preoperative sedation in children: a pharmacokinetic-pharmacodynamic analysis

Abstract: Studies of midazolam should evaluate the contribution of 1-OHMDZ to the overall PD effect. The metabolite 1-OHMDZ has approximately half the activity of the parent drug and can compensate for at least part of the decreased effect due to increased midazolam metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 44 publications
(33 reference statements)
1
24
0
Order By: Relevance
“…There are PKPD relationships described for short‐term intravenous midazolam in adults, using an EEG signal as an effect measure (31–33). These relationships are more difficult to describe after midazolam infusion administration over longer term in intensive care because the 1‐hydroxy metabolite has approximately half the activity of the parent drug (34).…”
Section: Discussionmentioning
confidence: 99%
“…There are PKPD relationships described for short‐term intravenous midazolam in adults, using an EEG signal as an effect measure (31–33). These relationships are more difficult to describe after midazolam infusion administration over longer term in intensive care because the 1‐hydroxy metabolite has approximately half the activity of the parent drug (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although LC-UV has been used for decades for the above purpose, these methodologies typically represent relatively poor sensitivity and low throughput, with a reported sensitivity of 1.0-100 ng/mL, sample size of up to 2.0 mL, and analysis cycle time of up to 18 min (Blackett et al, 1988;Carrillo et al, 1998;El Mahjoub and Staub, 2000;Ha et al, 1993;Johnson et al, 2002;Lee and Charles, 1996;Odou et al, 1997;Mastey et al, 1994;Portier et al, 1999;Puglisi et al, 1985;Sautou et al, 1991;ter Horst et al, 2003;van Brandt et al, 1997;Vletter et al, 1990;Yasui-Furukori et al, 2004). GC-MS methods appear to be more sensitive than HPLC-UV with a reported LLOQ of 20 pg/ mL for both midazolam and 1′-hydroxymidazolam when 1 mL of human plasma was used.…”
Section: Introductionmentioning
confidence: 99%
“…Pre- and post-operative blood samples in previously cannulated children (median age 5 years) receiving a general anaesthetic were taken and compared with the preoperative sedation score (1 = awake; 2 = drowsy/asleep). It was known that children have an increased weight-normalised clearance of midazolam (via CYP3A4) 8. These data showed that, despite a significant contribution to preoperative sedation by an active metabolite of midazolam (1-hydroxy-midazolam), a dose increase of up to 50% may be necessary to avoid therapeutic failure 8…”
mentioning
confidence: 98%